First clinical assessment of a prototype assay to detect the enzymatic activity of β-lactamase as a marker for pulmonary tuberculosis - Nabeta, Pamela; Seshadri, Pratibha; Havumaki, Joshua; Mbhele, Silindile; Hendricks, Layla; Perkins, Mark D.; Nicol, Mark P.; Denkinger, Claudia M. (Diagnostic microbiology and infectious disease, 2020)
The objective was to evaluate the sensitivity and specificity of a novel prototype test, TB REaD™, a reporter enzyme fluorescence-based assay, for pulmonary tuberculosis and to determine the optimal threshold for test positivity. This blinded, prospective study enrolled 250 patients, of which 23.2% were Mycobacterium tuberculosis complex (MTB) culture-positive. At the manufacturer-set threshold, sensitivity of the assay was 93.1% (95% confidence interval [CI] 83.3-98.1) and specificity was 8.9% (95% CI 5.2-13.8). The highest accuracy was seen at a higher threshold: sensitivity 58.6% (95% CI 44.9-71.4), specificity 59.4% (95% CI 52.1%-66.4%), with sensitivity by smear status being 40.0% (95% CI 21.1-61.3) for smear-negative and 72.7% (95% CI 54.5-86.7) for smear-positive. This study demonstrated limited accuracy of the TB REaD™ prototype for detection of pulmonary TB. Further improvements are necessary, potentially exploring probes that are more specific to MTB.
Gesehen am 18.09.2020